The Invention of 'Outsider Art' : Experiencing Practices of Othering in Contemporary Art Worlds in the UK - Scherr, Marion, 1988- (Image (Transcript (Firm)), 2022)
What does it mean to be called an "outsider"? Marion Scherr investigates structural inequalities and the myth of the Other in Western art history, examining the role of 'Outsider Art' in contemporary art worlds in the UK. By shifting the focus from art world professionals to those labelled "Outsider Artists", she counteracts one-sided representations of them being otherworldly, raw, and uninfluenced. Instead, the artists are introduced as multi-faceted individuals in constant exchange with their social environment and as employing diverse strategies in dealing with their exclusion. The book reframes their voices and artworks as complex, serious and meaningful cultural contributions, and challenges their attested Otherness in favour for a more inclusive, all-encompassing understanding of art.